EFEKTIVITAS UNDANG-UNDANG NOMOR 12 TAHUN 2022 TENTANG TINDAK PIDANA KEKERASAN SEKSUAL DALAM PERLINDUNGAN KORBAN PEREMPUAN - Giyono, Urip; Nurkhasanah, Sofiyatun; Rahman, Nur (Fakultas Hukum Universitas Muhammadiyah Cirebon, 2024)
Sexual violence in Indonesia has become a persistent issue that shows no signs of abating. Every day, cases of sexual violence continue to rise, with the majority of victims being women and children. This situation prompted the government to enact and implement Law No. 12 of 2022 on Sexual Violence Crimes. One of the primary objectives of this law is to provide optimal and comprehensive protection and recovery for victims. This study employs a normative-empirical method, analyzing the implementation of positive law provisions (legislation) and written documents in action (factually) in the context of specific legal events occurring in society. The findings indicate that the Sexual Violence Crimes Law has not yet been effective. Several contributing factors include weak law enforcement, inadequate facilities and recovery access for victims, and, in some cases, violations of victims' confidentiality. Keywords: Female Victims, Sexual Violence Crimes, Legal Protection